APPLICABILITY OF THE FMEA TOOL IN THE MITIGATION OF AGRICULTURAL PRODUCTIVE PROCESS FAILURES 4.0 - Bononi, Daniele Fernanda; Quero Polli, Henrique (Revista Interface Tecnológica, 2020)
Current technology, with new forms of work and several specific sectors, has been able to reach the agriculture sector, as, as is known, agribusiness is one of the pillars of Brazil’s economy. The article discusses a quality tool that helps the implementation of this technology, the FMEA (Failure Mode and Effect Analysis), which seeks to reduce and analyze the failures early in the production process, analyzing its application in Agroindustry 4.0. We conclude that, the correct planning and application of quality management tools, such as FMEA, early in the design of a production chain within Agroindustry 4.0, help in preventing possible design and execution failures, reducing waste, giving agility to the agribusiness industry and bringing Agroindustry closer to the process excellence sought after joining the 4.0 system.